2020
DOI: 10.1039/c9tb02863c
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired hybrid network hydrogel for continuous adhesion in water

Abstract: The mussel-inspired catechol-based strategy has been widely used in the development of adhesives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…This extraction or elusion technique is a well-known method to study the cytocompatibility of different types of implants. [57,58] XTT results showed excellent cell viability for the 3D printed substrates both before and after the grafting procedure (Figure 9a,b) demonstrating their high cytocompatibility. For a more intuitive visualization of the cell viability, we further performed the live-dead staining assay on 3T3 cells treated with the extracted DMEM (24 h incubation with the constructs) for 24 h of culture (Figure 9c-f) using staining with fluorescein diacetate, a cell membrane dye indicating live cells (green), and propidium iodide, a DNA stain indicating dead cells (red).…”
Section: Rendering the Stent With Anti-fouling Behaviormentioning
confidence: 96%
“…This extraction or elusion technique is a well-known method to study the cytocompatibility of different types of implants. [57,58] XTT results showed excellent cell viability for the 3D printed substrates both before and after the grafting procedure (Figure 9a,b) demonstrating their high cytocompatibility. For a more intuitive visualization of the cell viability, we further performed the live-dead staining assay on 3T3 cells treated with the extracted DMEM (24 h incubation with the constructs) for 24 h of culture (Figure 9c-f) using staining with fluorescein diacetate, a cell membrane dye indicating live cells (green), and propidium iodide, a DNA stain indicating dead cells (red).…”
Section: Rendering the Stent With Anti-fouling Behaviormentioning
confidence: 96%
“…The results of the vibration test show that the G ′ is significantly higher than the G “, thereby indicating that these hydrogels (FT3, FT6, and FT9) and Re‐gel behave more like a viscoelastic gel rather than a viscous fluid (Figure 8c). [ 45 ] Furthermore, G ′ increased with the FT cycles, which indicated that, to a certain extent, the rheological properties of the hydrogels depended on the FT cycles. Ice crystals might be formed and the NFLMP was present in frozen solutions of RHK at temperatures below the eutectic point of the corresponding system.…”
Section: Resultsmentioning
confidence: 97%
“…Fu et al [ 44 ] designed a hybrid system, based on CMC, to be used as an underwater adhesion hydrogel. For this purpose, oxidised CMC (OCMC) was prepared using the periodate oxidation method, and subsequently modified by combination with DA via carbodiimide (EDC/NHS) crosslinker chemistry (average DS = 15%).…”
Section: Resultsmentioning
confidence: 99%